Analysis of Variables Associated with Positive Micro-Embolic Signals Detected by Transcranial Doppler in Patients with Atrial Fibrillation and Their Predictive Value for Embolic Risk - Xu Y; Dong ZZ; Jiang LJ; Zhang CX; Dong GY (Dove Medical Press, 2023)
Yun Xu, Zhen-Zhen Dong, Li-Jiao Jiang, Cen-Xi Zhang, Guo-Ying Dong Department of Cardiology, Suzhou Wuzhong People's Hospital, Suzhou, 215128, People's Republic of ChinaCorrespondence: Cen-Xi Zhang, Department of Cardiology, Suzhou Wuzhong People's Hospital, No. 61 of Dongwu North Road, Wuzhong District, Suzhou, 215128, People's Republic of China, Tel +8618645767447, Email zhangcenxizzj@126.comObjective: This study examined the factors associated with positive micro-embolic signals (MES) on transcranial Doppler monitoring in patients with atrial fibrillation (AF), as well as the predictive value of MES for the risk of embolism in AF.Methods: Sixty-six patients who had micro emboli with AF were included in the positive group, and 75 patients who did not have micro emboli with AF served as the control group. The clinical data, congestive heart failure, hypertension, age ≥ 75 (doubled), diabetes mellitus, prior stroke or transient ischemic attack (doubled), vascular disease, age 65- 74, female (CHA2DS2-VASc) score, D-dimer (D-d) level, echocardiography results, and brain magnetic resonance imaging (MRI) findings were compared between the two groups. Logistic regression models were used to analyze the relationship between positive micro emboli with CHA2DS2-VASc score, D-d, left atrial anteroposterior diameter (LAD), and silent cerebral ischemia (SCI) occurrence.Results: The CHA2DS2-VASc score, D-d level, and LAD were significantly higher in the positive group than in the control group (P < 0.05) and were accompanied by a higher detection rate of SCI by brain MRI (P < 0.01). Elevated D-d levels, increased LAD, and the detection rate of SCI were all highly positively correlated with positive micro emboli. Also, CHA2DS2-VASc score ≥ 2 showed a significant positive correlation with positive micro emboli, and the higher CHA2DS2-VASc score was associated with a stronger correlation. The multivariate regression analysis demonstrated that positive micro-embolic was independently associated with SCI and a CHA2DS2-VASc score of ≥ 4.Conclusion: Positive micro emboli in patients with persistent AF are consistent with an increased risk of embolism, and are independently associated with a higher CHA2DS2-VASc score and SCI, which can be used as an indicator of individual embolic risk in patients with AF.Keywords: atrial fibrillation, AF, CHA2DS2-VASc score, D-dimer, left atrial anteroposterior diameter, micro-embolic signal, MES, silent cerebral ischemia